The Design of Tachometer Contact and Non-Contact Using Microcontroller - Tatiya Padang Tunggal; Lailicia Anggi Kirana; Afif Zuhri Arfianto; Elsayed T.Helmy; Farhad Waseel (Universitas Muhammadiyah Yogyakarta, 2020)
Calibration is required for various kinds of tools from kitchen tools such as stirrers or mixers to medical tools such as temperature calibration, ECG, blood pressure, and other instrumentation tools to be according to the required standards. In medical devices, a digital tachometer has been used as a calibration support device to measure the speed of objects that rotate in RPM on the centrifuge. Some medical devices are calibrated in km/hour, for example, the ergo cycle and treadmill. Two different devices or a conversion from RPM to km/hour are required. The research aimed to design a measurement device that performed calibration of devices with different units, namely tachometer that can be used to measure speed in RPM and km/hr. Based on the research objective, a tool was made to measure the motor's rotational speed using the E18-D80NK sensor, microcontroller, and LCD without touching the object being measured.